The Effect of Implementing Self-Management Education for Patients with Diabetes Mellitus in Controlling Blood Glucose Levels - Kurniawan, Rudi; Waluyo, Endrian Mulyadi Justitia; Srinayanti, Yanti; Yunitri, Ninik; Anwar, Syamsul; Herlinah, Lily (GLOBAL HEALTH SCIENCE GROUP, 2024)
With the increasing prevalence of diabetes mellitus, patient self-management education is an important concern. The aim of this study was to determine the effect of community-based self-management education on blood glucose levels in patients with diabetes mellitus. Method this study used a quasi-experimental design through a group pre-test and post-test design. The sampling technique was through convenience sampling, which amounted to 31 respondents. Data analysis includes univariate analysis, namely analysis of demographic data, and bivariate analysis to determine the effect of self-management education on lowering blood glucose levels using paired sample t-test. The results of the paired simple t-test with p-value <0.05 showed that there was a significant effect of self-management education on reducing blood glucose levels, knowledge level, behavior, visits to health facilities and medication adherence. However, there was no effect of self-management education on BMI. Conclusion Community-based self-management education has a significant effect on reducing blood glucose levels in patients with diabetes mellitus in the Ciamis Health Center working area.